Why do they go? Individual and corporate perspectives on the factors influencing the decision to accept an international assignment - Dickmann, Michael; Doherty, Noeleen; Mills, Timothy; Brewster, Chris (Taylor & Francis, 2008)
This article explores the motives of individuals to accept international assignments. It uses a combination of qualitative and quantitative research methods to further our understanding of how important a variety of items are in the decision to work abroad. Employing a mutual dependency perspective it contrasts individual motives and organizational perspectives. Organizations significantly underestimate the importance of career, work/life balance and development considerations and overestimate the financial imperative and some family motives. The analysis showed that for individuals some of these factors significantly relate to outcome variables in terms of the perceived career capital accrued from assignments. The study presents a more nuanced picture of influence factors on the decision to go and advocates the use of context- sensitive, multiple perspectives. Practical implications for multinational organizations are discussed.
Keywords: individual mobility influences international HRM international mobility organizational mobility boundaryless career dual-career expatriate experience abroad families managers success models impact